Efficiency testing of Malaysian Takaful fund using Treynor's and Sharpe's ratio - Halim N.A.; Gazali N.; Yaso S.Z.; Ahmad W.M.A.W. (American Institute of Physics Inc., 2024)
Malaysian Takaful fund is a form of investment where investors are given the flexibility to choose their own risk tolerance and investment. Therefore, investors can also choose from a variety of funds to invest and raise money in certain portfolio. Efficiency testing is very important to assist investors in analyzing the risk and expected return of fund. Therefore, the Treynors and Sharpe's ratio method is used to test the fund's efficiency/performance towards volatility and variability, respectively. By Treynor's and Sharpe's ratio, myEquity funds show the best performance compared to others Malaysian Takaful funds. However, it still do not match the benchmark of Emas Shariah Index (FBMSI). 2020 Author(s).